Clinical and molecular response to alpha1‐oleate treatment in patients with bladder cancer - Farhan Haq; Samudra Sabari; Jaromir Háček; Antonín Brisuda; Ines Ambite; Michele Cavalera; Parisa Esmaeili; Murphy Lam Yim Wan; Shahram Ahmadi; Marek Babjuk; Catharina Svanborg (Cancer Medicine)
Abstract Background The tumoricidal complex alpha1‐oleate targets bladder cancer cells, triggering rapid, apoptosis‐like tumor cell death. Clinical effects of alpha1‐oleate were recently observed in patients with non‐muscle invasive bladder cancer (NMIBC), using a randomized, placebo‐controlled study protocol. Aims To investigate if there are dose‐dependent effects of alpha1‐oleate. Materials and Methods Here, patients with NMIBC were treated by intravesical instillation of increasing concentrations of alpha1‐oleate (1.7, 8.5, or 17 mM) and the treatment response was defined relative to a placebo group. Results Strong, dose‐dependent anti‐tumor effects were detected in alpha1‐oleate treated patients for a combination of molecular and clinical indicators; a complete or partial response was detected in 88% of tumors treated with 8.5 mM compared to 47% of tumors treated with 1.7 mM of alpha1‐oleate. Uptake of alpha1‐oleate by the tumor triggered rapid shedding of tumor cells into the urine and cell death by an apoptosis‐like mechanism. RNA sequencing of tissue biopsies confirmed the activation of apoptotic cell death and strong inhibition of cancer gene networks, including bladder cancer related genes. Drug‐related side effects were not recorded, except for local irritation at the site of instillation. Discussion and Conclusions These dose‐dependent anti‐tumor effects of alpha1‐oleate are promising and support the potential of alpha1‐oleate treatment in patients with NMIBC.